High-thermal-conductivity composite sound-absorbing material as well as preparation method and application thereof
By filling the porous matrix of the speaker sound-absorbing material with high thermal conductivity and sound-absorbing material, and covering the three-dimensional nanothermal conduction mesh layer, the problem that existing sound-absorbing materials are difficult to take into account both thermal conductivity and sound-absorbing effects, and efficient heat dissipation and sound-absorbing effects are achieved.
Patent Information
- Application Number
- CN202411643367.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-28
AI Technical Summary
Existing speaker sound-absorbing materials are difficult to take into account high thermal conductivity and excellent sound-absorbing effects, and are prone to powder loss and powder leakage, affecting heat dissipation and sound-absorbing effects.
Porous materials are used as the substrate to fill high-thermal conductivity and sound-absorbing materials, and cover the three-dimensional nanothermal conduction mesh layer on the surface of the porous substrate to form a three-dimensional three-dimensional thermal conduction network to improve thermal conductivity and sound-absorbing effect, while suppressing the fall of sound-absorbing particles.
It realizes high thermal conductivity and excellent sound absorption effect of high thermal conductivity and high sound absorption effect of high thermal conductivity and long-term stability of the product, and is suitable for electronic devices such as speakers.
Smart Images

Figure CN119529375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sound-absorbing materials, and in particular to a high thermal conductivity composite sound-absorbing material and a preparation method and application thereof. Background Art
[0002] As an audio output device, speakers are widely used in various electronic devices such as speakers, televisions, car systems, mobile phones, computers, etc. However, speakers will generate a lot of heat during long-term use. The accumulation of heat will not only reduce the service life of the speakers, but also damage the sound quality of the speakers.
[0003] The sound-absorbing materials commonly used in the rear cavity of the speaker, such as molecular sieve sound-absorbing particles, do not have a heat dissipation function, and the sound-absorbing particles are prone to powder loss and leakage. They need to be configured through a powder filling process, and the equipment and process costs are high. In order to improve the heat dissipation problem of the speaker, high thermal conductivity materials such as graphene, carbon nanotubes, and carbon fibers are currently introduced to improve the heat dissipation capacity of the sound-absorbing particles. However, the specific surface area of such high thermal conductivity materials is much smaller than the specific surface area of the sound-absorbing particles. Under the same volume conditions, the sound absorption effect of the composite material formed by blending high thermal conductivity materials and sound-absorbing particles is not as good as that of a single sound-absorbing particle; in addition, in order to reduce the adverse effects of powder loss and leakage on heat dissipation and sound absorption, adhesives need to be introduced during the molding process to bond high thermal conductivity materials and sound-absorbing particles. The introduction of adhesives will reduce the specific surface area of the molecular sieve and affect the sound absorption effect of the sound-absorbing particles. In addition, adhesives are usually polymer materials with poor thermal conductivity, which will further affect the thermal conductivity of the composite material. Therefore, it is difficult for current sound-absorbing materials to take into account both thermal conductivity and sound absorption effects.
[0004] Based on this, there is an urgent need for a sound-absorbing material that has both high thermal conductivity and excellent sound absorption effects to meet the sound absorption and heat dissipation needs of electronic devices such as speakers. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high thermal conductivity composite sound-absorbing material and a preparation method and application thereof. The present invention uses a porous material as a matrix, and confines a high thermal conductivity material and a sound-absorbing material in the pores of the porous material to improve the thermal conductivity and sound absorption effect of the porous material; at the same time, by coating the outer surface of the porous matrix with a three-dimensional nano-thermal conductive mesh layer, the falling of the sound-absorbing particles is effectively suppressed without the use of an adhesive, which can further improve the sound absorption effect of the product and its long-term stability; and the three-dimensional nano-thermal conductive mesh layer can form a three-dimensional thermal conductive network with the nano-thermal conductive layer in the pores, further improving the heat dissipation capacity of the product, so that the product has good application prospects in electronic devices with sound absorption and heat dissipation requirements such as speakers.
[0006] Specifically, the following technical solutions are provided:
[0007] The first aspect of the present invention provides a high thermal conductivity composite sound-absorbing material, the high thermal conductivity sound-absorbing material comprising a porous matrix, a heat dissipation and sound-absorbing composite layer formed in the pores of the porous matrix, and a three-dimensional nano-thermal conductive mesh layer formed on the outer surface of the porous matrix;
[0008] The heat dissipation and sound absorption composite layer comprises a nano heat conductive layer and a sound absorption particle layer which are stacked.
[0009] Furthermore, the heat dissipation and sound absorption composite layer comprises a plurality of alternately stacked nano heat conductive layers and sound absorption particle layers, and at least one nano heat conductive layer is in contact with the porous matrix skeleton.
[0010] The present invention sets a nano-thermal conductive layer on the porous matrix skeleton (including the inner wall of the internal pores). The high thermal conductivity material contained in the nano-thermal conductive layer can effectively improve the thermal conductivity of the porous matrix, and at the same time, it can form a three-dimensional thermal conductive network with the three nano-thermal conductive mesh layers coated on the outer surface of the porous matrix, further improving the heat dissipation capacity of the composite sound-absorbing material. In addition, in some preferred embodiments of the present invention, the heat dissipation attraction composite layer includes n+1 layers of nano-thermal conductive layers and n layers of sound-absorbing particle layers alternately stacked, n is greater than or equal to 1, and any sound-absorbing particle layer forms a sandwich structure with the adjacent nano-thermal conductive layer, which is conducive to improving the stability of the sound-absorbing material filled in the pores of the porous matrix.
[0011] Furthermore, the porous matrix is preferably polymer foam, foam metal or porous carbon material, such as polyurethane sound-absorbing foam, but is not limited to the types listed above, and may also be other substrates with a porous structure.
[0012] Furthermore, the nano thermally conductive layer comprises a first thermally conductive material, which may be selected from one or more of graphene, carbon nanotubes, carbon fibers, carbon black, graphite, silver nanowires, and copper nanowires; more preferably, the first thermally conductive material is a one-dimensional nanomaterial and / or a two-dimensional nanomaterial.
[0013] Furthermore, the sound-absorbing particle layer contains sound-absorbing materials, which include but are not limited to one or more of molecular sieve powder, mesoporous silica, and carbon nanotubes, such as ZSM-5 molecular sieve.
[0014] Furthermore, the three-dimensional nano thermally conductive mesh layer contains a second thermally conductive material, which is a one-dimensional nanomaterial. Preferably, the one-dimensional nanomaterial is selected from one or more of silver nanowires, gold nanowires, copper nanowires, carbon nanotubes, and carbon fibers.
[0015] Furthermore, the size of the first thermally conductive material is smaller than the size of the porous matrix pore size, and the size of the second thermally conductive material is larger than the size of the first thermally conductive material; wherein, size refers to the average particle size of granular materials, the average length of one-dimensional materials or the average diameter (lateral dimension) of two-dimensional materials, the porous matrix pore size is the pore diameter of the porous matrix, and the porous matrix pore size is the pore diameter of the porous matrix.
[0016] In some preferred embodiments, the size of the first thermally conductive material is 50 nm-100 μm, the pore size of the porous matrix is 50 μm-500 μm, and the size of the second thermally conductive material is 10 μm-200 μm.
[0017] Furthermore, the pores of the three-dimensional nano-thermal conductive mesh layer are smaller than the particle size of the sound absorbing material. Preferably, the particle size of the sound absorbing material is 1 μm-10 μm, and the pore size of the three-dimensional nano-thermal conductive mesh layer is 50nm-500nm.
[0018] In the present invention, the size of the first thermally conductive material included in the nano thermally conductive layer is preferably smaller than the size of the pore size of the porous matrix, so that the first thermally conductive material can enter the internal pores of the porous matrix through the pores of the porous matrix, and be adsorbed on the inner wall of the internal pores of the porous matrix to form a nano thermally conductive layer; and the size of the second thermally conductive material included in the three-dimensional nano thermally conductive mesh layer is preferably larger than the size of the first thermally conductive material, so that most of the second thermally conductive material can be interwoven on the surface of the porous matrix to form a three-dimensional thermally conductive network, and the formed three-dimensional nano thermally conductive mesh layer can close the pore openings of the porous matrix, so that the pores of the three-dimensional nano thermally conductive mesh layer are smaller than the particle size of the sound-absorbing material, so that without using an adhesive, the sound-absorbing material can be effectively inhibited from falling out of the pores of the porous matrix, which is beneficial to improving the sound absorption effect and thermal conductivity of the composite sound-absorbing material.
[0019] The second aspect of the present invention provides a method for preparing the high thermal conductivity composite sound-absorbing material according to the first aspect, comprising the following steps:
[0020] (1) immersing the porous substrate in a dispersion of a first thermally conductive material, taking it out and drying it, so that the first thermally conductive material adsorbed on the porous substrate skeleton forms a nano thermally conductive layer, thereby obtaining a modified porous substrate A;
[0021] (2) immersing the modified porous substrate A prepared in step (1) in a dispersion of a sound-absorbing material, taking it out and drying it, and the sound-absorbing material adsorbed on the nano-thermal conductive layer of the modified porous substrate A forms a sound-absorbing particle layer, thereby obtaining a modified porous substrate B;
[0022] (3) Optionally, repeat step (1) or repeat steps (1) and (2) several times to obtain a modified porous matrix C;
[0023] (4) forming a three-dimensional nano-thermal conductive mesh layer on the outer surface of the modified porous matrix B or the modified porous matrix C by dipping, spraying, printing, inkjet printing, coating or dispensing the second thermally conductive material to obtain the high thermal conductivity composite sound-absorbing material.
[0024] Furthermore, in step (1), the mass concentration of the first thermally conductive material dispersion is 0.5%-2.5%.
[0025] Furthermore, in step (1), the immersion time is 5-15 minutes.
[0026] Furthermore, in step (1), the drying temperature is 80-120° C., and the drying time is 5-15 min.
[0027] Furthermore, in step (2), the mass concentration of the sound absorbing material dispersion is 5%-15%.
[0028] Furthermore, in step (2), the immersion time is 5-15 minutes.
[0029] Furthermore, in step (2), ultrasonic treatment is performed during the impregnation process to assist the sound absorbing material to enter the pores of the modified porous matrix A.
[0030] Furthermore, in step (2), the drying temperature is 80-120° C., and the drying time is 5-15 min.
[0031] Furthermore, in step (4), the impregnation method is specifically as follows: the modified porous matrix B prepared in step (2) or the modified porous matrix C prepared in step (3) is immersed in a second thermally conductive material dispersion, taken out and dried, and the second thermally conductive material coated on the surface of the modified porous matrix B or the modified porous matrix C forms a three-dimensional thermally conductive network layer to obtain the high thermal conductivity composite sound-absorbing material; preferably, the mass concentration of the second thermally conductive material dispersion is 0.5%-5%, and the impregnation time is 5-15min.
[0032] A third aspect of the present invention provides a speaker, comprising a sound-absorbing material fixedly arranged at a preset position of the speaker, wherein the sound-absorbing material is the high thermal conductivity composite sound-absorbing material described in the first aspect or the high thermal conductivity composite sound-absorbing material prepared by the preparation method described in the second aspect.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention provides a high thermal conductivity composite sound-absorbing material, which takes a porous material as a matrix, and fills the pores of the porous matrix with a high thermal conductivity material and a sound-absorbing material in a specific structure, thereby improving the thermal conductivity and sound-absorbing effect of the porous material. At the same time, the composite sound-absorbing material is obtained by coating a three-dimensional nano thermal conductive mesh layer on the surface of the porous matrix, which effectively suppresses the falling of sound-absorbing particles without using an adhesive, and can further improve the sound absorption effect and long-term stability of the product; and the three-dimensional nano thermal conductive mesh layer can form a three-dimensional thermal conductive network with the nano thermal conductive layer in the pores, further improving the heat dissipation capacity of the product, so that the product has good application prospects in electronic devices with sound absorption and heat dissipation requirements such as speakers.
[0035] In addition, the high thermal conductivity composite sound-absorbing material provided by the present invention can be prepared by simple multiple impregnations. The preparation method is simple, easy to operate, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 A schematic diagram of the local structure of the internal pores of the high thermal conductivity composite sound-absorbing material prepared in Example 1;
[0037] Figure 2 This is a SEM image of the polyurethane sound-absorbing foam in Example 1, with a magnification of 100;
[0038] Figure 3 This is a SEM image of the ZSM-5 molecular sieve in Example 1, with a magnification of 5000;
[0039] Figure 4 This is a SEM image of the high thermal conductivity composite sound-absorbing material prepared in Example 1, with a magnification of 1000;
[0040] Figure 5 This is a SEM image of the high thermal conductivity composite sound-absorbing material prepared in Example 1, with a magnification of 5000;
[0041] Figure 6 It is a schematic diagram of the local structure of the internal pores of a high thermal conductivity composite sound-absorbing material;
[0042] Figure 7 It is a schematic diagram of the local structure of the internal pores of a high thermal conductivity composite sound-absorbing material;
[0043] Icon: 1 is the inner wall of the pore, 2 is the nano-thermal conductive layer, and 3 is the sound-absorbing particle layer. DETAILED DESCRIPTION
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0045] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0046] Example 1
[0047] This embodiment provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof, and the specific operations are as follows:
[0048] (1) Soak the polyurethane sound-absorbing foam (pore size 200-500 μm) in a dispersion of graphene (size distribution 50 nm-40 μm) with a mass concentration of 1% (solvent is water) for 5 min, then take it out and place it on a sieve, and bake it in an oven at 120°C for 10 min. Figure 1 As shown, a nano heat-conducting layer 2 is formed on the inner wall 1 of the pores inside the polyurethane sound-absorbing foam to obtain a modified polyurethane sound-absorbing foam A;
[0049] (2) The modified polyurethane sound-absorbing foam A prepared in step (1) is immersed in a dispersion (solvent is water) of ZSM-5 molecular sieve (particle size is about 1.5 μm) with a mass concentration of 10%, and ultrasonic dispersion can be used to assist the molecular sieve to enter the internal pores of the modified polyurethane sound-absorbing foam A. The immersion time is 5 min, and then the modified polyurethane sound-absorbing foam A is taken out and placed on a sieve, and then placed in an oven for baking at 120° C. for 10 min. A sound-absorbing particle layer 3 is formed on the side of the nano-thermal conductive layer 2 away from the pore inner wall 1, thereby obtaining a modified polyurethane sound-absorbing foam B;
[0050] (3) The modified polyurethane sound-absorbing foam B prepared in step (2) is immersed in a dispersion of silver nanowires (size distribution 15-20 μm) with a mass concentration of 1% (the solvent is water), so that the silver nanowires are wrapped around the external pores of the foam. The immersion time is 5 min, and then the foam is taken out and placed on a sieve, and then placed in an oven for baking. The drying conditions are 120° C. and 10 min to obtain a high thermal conductivity composite sound-absorbing foam.
[0051] The SEM image of the high thermal conductivity composite sound-absorbing foam in this embodiment is as follows: Figure 1 As shown, graphene with a relatively small size enters the internal pores of the polyurethane sound-absorbing foam ( Figure 2 ), and the nano-thermal conductive layer is formed by bonding with the inner wall of the foam pores. The smaller sound-absorbing particles enter the foam pores through impregnation and are adsorbed on the nano-thermal conductive layer to form a sound-absorbing particle layer. Finally, the silver nanowires form a dense three-dimensional heat-conductive network layer on the outer surface of the modified polyurethane sound-absorbing foam B ( Figure 4 , 5 ), closing part of the pore openings of the porous matrix.
[0052] In addition, in some preferred embodiments, the operation of step (1) can be repeated before step (3) to prepare Figure 6 The high thermal conductivity composite sound-absorbing material having a first nano-thermal conductive layer, a sound-absorbing particle layer, and a second nano-thermal conductive layer in a stacked arrangement. Alternatively, steps (1) and (2) are repeated before step (3) to prepare Figure 7 The heat dissipation and sound absorption composite layer shown has a first nano heat conductive layer, a first sound absorbing particle layer, a second nano heat conductive layer, and a second sound absorbing particle layer which are stacked.
[0053] Example 2
[0054] This embodiment provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof. The difference from the first embodiment is that the type of the first thermal conductive material is different, and an equal amount of one-dimensional carbon nanotubes with a size distribution of 50-5000 nm are used to replace the two-dimensional graphene. The other operations are the same. The specific operations are as follows:
[0055] (1) The polyurethane sound-absorbing foam (pore size 200-500 μm) was immersed in a dispersion of carbon nanotubes (size distribution 50-100 μm) with a mass concentration of 1% (solvent is water) for 5 min, then taken out and placed on a sieve, and baked in an oven at 120°C for 10 min. Figure 1 As shown, a nano heat-conducting layer 2 is formed on the inner wall 1 of the pores inside the polyurethane sound-absorbing foam to obtain a modified polyurethane sound-absorbing foam A;
[0056] (2) The modified polyurethane sound-absorbing foam A prepared in step (1) is immersed in a dispersion (solvent is water) of ZSM-5 molecular sieve (particle size is about 1.5 μm) with a mass concentration of 10%, and ultrasonic dispersion can be used to assist the molecular sieve to enter the internal pores of the modified polyurethane sound-absorbing foam A. The immersion time is 5 min, and then the modified polyurethane sound-absorbing foam A is taken out and placed on a sieve, and then placed in an oven for baking at 120° C. for 10 min. A sound-absorbing particle layer 3 is formed on the side of the nano-thermal conductive layer 2 away from the pore inner wall 1, thereby obtaining a modified polyurethane sound-absorbing foam B;
[0057] (3) The modified polyurethane sound-absorbing foam B prepared in step (2) is immersed in a dispersion of silver nanowires (size distribution 15-20 μm) with a mass concentration of 1% (the solvent is water), so that the silver nanowires are wrapped around the external pores of the foam. The immersion time is 5 min, and then the foam is taken out and placed on a sieve, and then placed in an oven for baking. The drying conditions are 120° C. and 10 min to obtain a high thermal conductivity composite sound-absorbing foam.
[0058] Example 3
[0059] This embodiment provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof. The difference from Embodiment 1 is that the type of the first thermal conductive material is different, and an equal amount of carbon black of similar size is used to replace the two-dimensional material graphene. The other operations are the same. The specific operations are as follows:
[0060] (1) Soak the polyurethane sound-absorbing foam (pore size 200-500 μm) in a dispersion of carbon black (size distribution 10-80 μm) with a mass concentration of 1% for 5 min, then take it out and place it on a sieve, and bake it in an oven at 120°C for 10 min. Figure 1 As shown, a nano heat-conducting layer 2 is formed on the inner wall 1 of the pores inside the polyurethane sound-absorbing foam to obtain a modified polyurethane sound-absorbing foam A;
[0061] (2) The modified polyurethane sound-absorbing foam A prepared in step (1) is immersed in a dispersion of ZSM-5 molecular sieve (particle size of about 1.5 μm) with a mass concentration of 10%. Ultrasonic dispersion can be used to assist the molecular sieve to enter the internal pores of the modified polyurethane sound-absorbing foam A. The immersion time is 5 min. The foam is then taken out and placed on a sieve. The foam is placed in an oven and baked at 120° C. for 10 min. A sound-absorbing particle layer 3 is formed on the side of the nano-thermal conductive layer 2 away from the pore inner wall 1 to obtain a modified polyurethane sound-absorbing foam B.
[0062] (3) The modified polyurethane sound-absorbing foam B prepared in step (2) is immersed in a dispersion of silver nanowires (size distribution 15-20 μm) with a mass concentration of 1%, so that the silver nanowires are wrapped around the external pores of the foam. The immersion time is 5 min, and then the foam is taken out and placed on a sieve, and then placed in an oven for baking. The drying conditions are 120° C. and 10 min to obtain a high thermal conductivity composite sound-absorbing foam.
[0063] Comparative Example 1
[0064] This comparative example provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof, which is different from Example 1 only in that the graphene and molecular sieve in steps (1) and (2) are uniformly mixed in water to obtain a uniformly mixed dispersion (the mass concentration of graphene is 1%, and the mass concentration of molecular sieve is 10%), and a one-step impregnation is performed. The remaining operations are the same to prepare the corresponding high thermal conductivity composite sound-absorbing material.
[0065] Comparative Example 2
[0066] This comparative example provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof, which is different from Example 1 only in that step (3) is not included, and the remaining operations are the same to prepare the corresponding high thermal conductivity composite sound-absorbing material.
[0067] Comparative Example 3
[0068] This comparative example provides a high thermal conductivity composite sound-absorbing material and a preparation method thereof, which is different from Example 1 only in that step (1) is not included, and the remaining operations are the same to prepare the corresponding high thermal conductivity composite sound-absorbing material.
[0069] Performance Testing
[0070] The thermal conductivity, sound absorption performance and structural stability of the high thermal conductivity composite sound-absorbing materials prepared in the above embodiments and comparative examples were tested. The specific test process is as follows:
[0071] Vertical thermal conductivity test: The equipment used is LW-9389 steady-state heat flow thermal conductivity tester, referring to ASTM-D5470 "Standard Test Method for Thermal Transfer Properties of Thermally Conductive Electrical Insulating Materials", the sample is cut into a 3mm×3mm square piece, and the thermal conductive sheet-thermal conductivity test mode is selected to test the thermal conductivity of the graphene foam.
[0072] Specific surface area test: Referring to ISO 9277-2010, the specific surface area of the foam was tested using the gas adsorption BET method. The pretreatment condition of the foam was baking at 100°C for 24 hours.
[0073] Drop test: Cut the high thermal conductivity composite sound-absorbing material into a 6mm×10mm rectangle with a thickness of 1mm. Put the sample into a speaker cavity of appropriate size and make the cavity drop from a height of about 10cm. Test 10 times in total. After the drop test, if the foam is not damaged and no molecular sieve powder falls out, it is judged as OK, otherwise it is judged as NG.
[0074] The test results are shown in Table 1 below:
[0075] Table 1
[0076]
[0077] It can be seen from Table 1 that the high thermal conductivity composite sound-absorbing materials prepared in Examples 1-3 have both high thermal conductivity and high specific surface area (the higher the specific surface area, the better the sound absorption effect), and maintain good structural stability in the drop test without powdering. It can be seen that the high thermal conductivity composite sound-absorbing material provided by the present invention can effectively suppress the falling of sound-absorbing particles without using an adhesive.
[0078] It can be seen from Example 1 and Comparative Example 1 that the first thermal conductive material graphene is directly mixed evenly with the sound-absorbing particle molecular sieve, a one-step blending impregnation is performed, and then the composite material prepared by coating the silver nanowire mesh layer (Comparative Example 1) has a greatly reduced thermal conductivity and specific surface area compared to the embodiment; this is because when graphene and molecular sieve are mixed, the pores on the surface of the molecular sieve will be covered by graphene, thereby greatly reducing the specific surface area of the composite material, and the disordered distribution between the molecular sieve and the graphene further affects the thermal conductivity of the composite material.
[0079] In addition, compared with Example 1, the specific surface area of the composite sound-absorbing material prepared in Comparative Example 2 without the silver nanowire mesh layer coating treatment did not change significantly, but the thermal conductivity and structural stability of the composite sound-absorbing material decreased significantly, and serious powder loss occurred in the drop test, which would further affect the long-term stability of the sound absorption effect of the composite sound-absorbing material. The specific surface area and structural stability of the composite sound-absorbing material (Comparative Example 3) that does not contain a nano thermal conductive layer in the foam pores did not change significantly compared with Example 1, but the thermal conductivity decreased.
[0080] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A high thermal conductivity composite sound-absorbing material, characterized in that: The high thermal conductivity composite sound-absorbing material comprises a porous matrix, a heat dissipation and sound-absorbing composite layer formed in the pores of the porous matrix, and a three-dimensional nano heat-conducting mesh layer formed on the outer surface of the porous matrix; The heat dissipation and sound absorption composite layer comprises a nano heat conductive layer and a sound absorption particle layer which are stacked.
2. The high thermal conductivity composite sound-absorbing material according to claim 1, characterized in that: The heat dissipation and sound absorption composite layer comprises a plurality of alternately stacked nano heat conductive layers and sound absorption particle layers, and at least one nano heat conductive layer is in contact with the inner wall of the pores of the porous matrix.
3. The high thermal conductivity composite sound-absorbing material according to claim 1, characterized in that: The porous matrix is a polymer foam, a foam metal or a porous carbon material; The nano thermally conductive layer comprises a first thermally conductive material, and the first thermally conductive material is selected from one or more of graphene, carbon nanotubes, carbon fibers, carbon black, graphite, silver nanowires, and copper nanowires; preferably, the first thermally conductive material is a one-dimensional nanomaterial and / or a two-dimensional nanomaterial; The sound-absorbing particle layer comprises a sound-absorbing material, and the sound-absorbing material is selected from one or more of molecular sieve powder, mesoporous silica, and carbon nanotubes; The three-dimensional nano thermally conductive mesh layer comprises a second thermally conductive material, which is a one-dimensional nanomaterial. Preferably, the one-dimensional nanomaterial is selected from one or more of silver nanowires, gold nanowires, copper nanowires, carbon nanotubes, and carbon fibers.
4. The high thermal conductivity composite sound-absorbing material according to claim 3, characterized in that: The size of the first thermally conductive material is smaller than the size of the pore size of the porous matrix, and the size of the second thermally conductive material is larger than the size of the first thermally conductive material; wherein the size is the average particle size of the granular material, the average length of the one-dimensional material, or the average diameter of the two-dimensional material; Preferably, the size of the first heat-conducting material is 50 nm-100 μm, the pore size of the porous matrix is 50 μm-500 μm, and the size of the second heat-conducting material is 10 μm-200 μm.
5. The high thermal conductivity composite sound-absorbing material according to claim 3 or 4, characterized in that: The pores of the three-dimensional nano heat-conducting mesh layer are smaller than the particle size of the sound-absorbing material; Preferably, the particle size of the sound absorbing material is 1 μm-10 μm; the pore size of the three-dimensional nano heat conductive mesh layer is 50 nm-500 nm.
6. A method for preparing the high thermal conductivity composite sound-absorbing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) immersing the porous substrate in a dispersion of a first thermally conductive material, taking it out and drying it, so that the first thermally conductive material adsorbed on the porous substrate skeleton forms a nano thermally conductive layer, thereby obtaining a modified porous substrate A; (2) immersing the modified porous substrate A prepared in step (1) in a dispersion of a sound-absorbing material, taking it out and drying it, and the sound-absorbing material adsorbed on the nano-thermal conductive layer of the modified porous substrate A forms a sound-absorbing particle layer, thereby obtaining a modified porous substrate B; (3) Optionally, repeat step (1) or repeat steps (1) and (2) several times to obtain a modified porous matrix C; (4) Forming a three-dimensional thermal conductive mesh layer on the outer surface of the modified porous substrate B or the modified porous substrate C by dipping, spraying, printing, inkjet printing, coating or dispensing the second thermal conductive material to obtain the high thermal conductive composite sound-absorbing material.
7. The preparation method according to claim 6, characterized in that: In step (1), at least one of the following features is included: (1) The mass concentration of the first thermally conductive material dispersion is 0.5%-2.5%; (2) The immersion time is 5-15 minutes; (3) The drying temperature is 80-120° C. and the drying time is 5-15 min.
8. The preparation method according to claim 6, characterized in that: In step (2), at least one of the following features is included: (1) The mass concentration of the sound absorbing material dispersion is 5%-15%; (2) The immersion time is 5-15 minutes; (3) performing ultrasonic treatment during the impregnation process to assist the sound absorbing material to enter the pores of the modified porous matrix A; (4) The drying temperature is 80-120° C. and the drying time is 5-15 min.
9. The preparation method according to claim 6, characterized in that: In step (4), the impregnation method is specifically: immersing the modified porous matrix B prepared in step (2) or the modified porous matrix C prepared in step (3) in a dispersion of the second thermally conductive material, taking it out and drying it, and the second thermally conductive material coated on the outer surface of the modified porous matrix B or the modified porous matrix C forms a three-dimensional nano-thermal conductive network layer to obtain the high thermal conductivity composite sound-absorbing material; Preferably, the mass concentration of the second thermally conductive material dispersion is 0.5%-5%, and the immersion time is 5-15 minutes.
10. A loudspeaker, characterized in that: It comprises a sound-absorbing material fixedly arranged at a preset position of the speaker, wherein the sound-absorbing material is the high thermal conductivity composite sound-absorbing material according to any one of claims 1 to 5 or the high thermal conductivity composite sound-absorbing material prepared by the preparation method according to any one of claims 6 to 9.